Accounting for the Ummah: The Role of Pesantren Accounting Knowledge in Financial Accountability - Nirwana, Ros; Anizar, Sriyunia; Jakiroh, Jakiroh; Bintari, Endah Sri (AKTIVA: Journal of Accountancy and Management, 2025)
Purpose: This research aims to test and analyze the influence of the Islamic Boarding School Accounting Guidelines on financial management accountability at Islamic Boarding Schools in Martapura City. Methodology: This type of research is qualitative research using primary data by distributing questionnaires to managers and employees at the Islamic Boarding School in Martapura city. The number of respondents collected was 32, with a data analysis technique, namely, simple linear regression analysis. Research Findings: The results of the research show that knowledge of the Islamic Boarding School Accounting Guidelines has a positive effect on financial management accountability in Islamic Boarding Schools. Contribution: This research contributed to the understanding of the importance of Islamic Boarding School Accounting Guidelines in improving financial management accountability. Tujuan Penelitian: Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh pengetahuan Pedoman Akuntansi Pondok Pesantren terhadap akuntabilitas pengelolaan keuangan pada Pondok Pesantren di Kota Martapura.Metodologi: Jenis penelitian ini adalah penelitian kualitatif dengan menggunakan data primer dengan menyebarkan kuesioner kepada pimpinan dan karyawan Pondok Pesantren di Kota Martapura. Jumlah responden yang terkumpul sebanyak 32 responden, dengan teknik analisis data yaitu analisis regresi linier sederhana.Temuan Penelitian: Hasil penelitian menunjukkan bahwa pengetahuan tentang Pedoman Akuntansi Pondok Pesantren berpengaruh positif terhadap akuntabilitas pengelolaan keuangan di Pondok Pesantren.Kontribusi: Penelitian ini memberikan kontribusi pada pemahaman tentang signifikansi Pedoman Akuntansi Pondok Pesantren dalam meningkatkan akuntabilitas pengelolaan keuangan di Pondok Pesantren.